The Level of Housewife's Knowledge about Antibiotic Use - Muhamad Adryan Farabi; M. Sidrotullah; Tri Puspita Roska; Andy Susbandiyah Ifada; Lale Syifaun Nufus (GLOBAL HEALTH SCIENCE GROUP, 2024)
Low knowledge about medications including the use of antibiotics can lead to the failure of therapy objectives. Improperly use of antibiotics can cause bacterial resistance. The correct use of antibiotics can be influenced by several factors, one of which is the level of knowledge. This study aims to determine the level of housewives' knowledge about antibiotic use in Dasan Tapen Induk Village, Gerung District, West Lombok Regency. Method: This research is a descriptive survey study, using purposive sampling technique. The sample consists of 77 respondents who meet the inclusion and exclusion criteria. Data from the respondents were collected using a questionnaire and analyzed quantitative descriptive. 41 respondents (53.25%) had good knowledge, 30 respondents (38.96%) had sufficient knowledge, and 6 respondents (7.79%) had poor knowledge. It can be concluded that the level of housewives' knowledge about antibiotic use is classified as good (53.25%).